Programmed obsolescence practices and their economic and environmental impacts - Abassi, Talel; Benkhedidja, Mouncef (Milev Journal of Research and Studies, 2019)
This paper addresses the issue of programmed obsolescence, which has become modern in recent years, in light of the tendency of most companies to adopt this strategy in order to increase sales and maintain its position in the market. The study reached the most important results that The institutions seek to achieve their goals by using any means, even at the expense of the environment and the consumer, which made them resort to programmed obsolescence despite its negative effects socially, economically and even environmentally.